Synthesis and Characterization of [2-(carboxy methylene-amino)-phenyl imino] acetic acid (L) and its some metal complexes - Baghdad Science Journal (مجلة بغداد للعلوم)
New Schiff base, namely [2-(carboxy methylene-amino)-phenyl imino] acetic acid (L) and its some metal complexes [LCo.2H2O], [LNi.2H2O], [LCu].3H2O, [LCd.2H2O], [LHg.2H2O] and [LPb.2H2O], were reported and characterized by elemental analysis, metal content, spectroscopic methods, magnetic moments and conductivity measurements, it is found that the geometrical structures of these complexes are octahedral [Co(II), Ni(II), Cd(II), Hg(II), Pb(II) and square planar Cu(II).The complexes have been found to posses 1:1 (M:L) stoichiometry